Part III. An appraisal of the planting programme, 1959-66 - Pollard, D F W (Wildfowl, 1967)
The production of food (seed) and cover by plants, introduced in the course of management of the W.A.G.B.I. Wildfowl Trust Experimental Reserve, was estimated in 1966. There were considerable differences between the yields of the sixteen species investigated, when food was assessed in terms of dry weight. In general, much higher yields could be obtained from agricultural crop species. The amount of food produced was inadequate to support the winter population of wildfowl observed; the prime function of the reserve was to act as a roost in the vicinity of alternative feeding areas. Considerable cover had been developed through planting, and appeared to be reflected in an increase in the breeding population. The moderate amount of food available may have been an important additional factor of the success of the reserve as a breeding station for wildfowl. On the basis of results obtained, recommendations are made for short- and long-term planting programmes for similar areas.